Rebounding Identities: The Politics of Identity in Russia and Ukraine - Chernetsky, Vitaly (A journal of church and state, 2009)
This collection brings together ten case studies examining the ethno-national, linguistic, and religious aspects of identity transformation in Russia and Ukraine. Bookended by a theoretical introduction and a summarizing conclusion by the volume's co-editors, the individual chapters by up-and-coming social scientists emphasize the contradictory nature of identity construction and performance, where state-sponsored attempts at regulation from above become entangled in a complex negotiation with impulses coming from below and from beyond the nation's territory., Paul Werth's contribution looks at Russian imperial bureaucracy's policies regarding religious conversion.